Regras de ocupação e influência de dopantes trivalentes em matrizes cerâmicas transparentes de PLZT 9/65/35 - Botero, Eriton Rodrigo (2009)
In this work, were investigated the occupancy of rare-earth ions in lattice site of the ferroelectric system (Pb,La)(Zr,Ti)O3, or PLZT. The influence on the structural, microestructural, dielectric, ferroelectric, optical and electro-optical properties, due to the aliovalent occupancy were also investigated. The rare-earth oxides (Nd2O3, Ho2O3, Er2O3, Tm2O3 e Yb2O3) were added, at 1.0 weight %, to the ceramic powders of PLZT (with La/Zr/Ti=9/65/35), synthesized by the conventional oxide mixing process, and then were re-calcined. The ceramic bodies, conformed from the milled powders, were densified by uniaxial hot pressing method. The properties of the ceramics were comparatively analyzed as a function of the rare-earth doping ions. The structural characterization, at room temperature, was made using the Rietveld refinement of the XRD patterns. In this way, for each composition, the effective stoichiometry, the lattice parameter and the crystalline symmetry were identified. The occupancy of the rare-earth ions were confirmed in the both, A and B, sites of the PLZT s perovskite structure (ABO3). The ionic occupancy is ruled by its atomic radii, pre-determined by Pauling rules for the structural stability. The effects of the aliovalent ionic occupancy were investigated using a novel parameter, the ―effective radius‖, defined as an average of the radius and the atomic concentration for each coordination number, i.e., a parameter which the geometric characteristic of the ion (ionic radius) and its molar content in each site are considered. In this way, it was observed that dopants with effective radius > 1.2 Å, as the Nd+3, preferentially occupy the A sites of the PLZT s perovskite structure. In this specific case, at room temperature, a cubic crystalline symmetry (paraelectric) was stabilized; a typical quadratic electro-optic effect and a slimloop polarization hysteresis were found. Up to 1.0 weight % of Nd2O3, ~1.9 mol % of Nd+3, were found no formation of segregated phase, that shows the ion stability in the crystalline lattice. The preferential occupancy of the A sites, as also in the case of the Ho+3, have the formation of lattice vacancies in the A sites, as consequence. The effects of these vacancies are the decrease of the polarization values and an increase of the diffusiveness of the phase transition. By the way, for doping ions with effective radius <1Å, as in the case of the Tm+3 and Yb+3, the preferential occupancy in the PLZT s perovskite structure are in the B sites. In such way, oxygen sites vacancies (VO) are originated. For these cases, an increase of the electrical polarization, the ferroelectric fatigue process and the linear electro-optic effect could be observed. In this case, for the doping content of 1.0 weight %, added in the PLZT s matrix, a formation of segregated phase and a consequent reduction the optical transmittance values can be observed. Dopants with intermediary effective radius, as the Er+3, have the lattice occupation in the both (A and B) sites equally divided, and the effects of this class of occupancy are mixed from the two cases discussed. Based on these results, it is proposed one limit for the trivalent ions occupancy in both A/B sites of the perovskite structure of the PLZT 9/65/35, where the effects of aliovalent ion substitution induce different changes in the properties of the ceramics.